A chemical evolution of NVP-containing VIPAR-family 3D polymer gel dosimeters – a brief overview. (August 2019) - Kozicki, M; Jaszczak, M; Maras, P; Dudek, M
Abstract: NVP-containing three-dimensional polymer gel dosimeters for radiotherapy dosimetry have been developed for more than 20 years. There have been 11 main modifications of the originally proposed VIPAR polymer gel dosimeter that altogether have amounted to 12 gel dosimeter formulae. This communication is to summarise the main chemical changes made to the VIPAR dosimeter over these years of research. The newest NVP-polymer gel dosimeters are also introduced.